Benefits and limitations of variance analysis in management accounting / Marzlin Marzuki ... [et al.] - Marzuki, Marzlin; Abdul Rahim, Noraini; Ismail, Jurina (Faculty of Accountancy, UiTM Kedah, 2019)
Adequate planning, monitoring and controlling of various activities in meeting organization objectives and goals are essential. One of the tools that could be used by management to monitor and control all activities at the operational level is by applying variance analysis. Referring to CIMA Official Terminology 2005, variance is the evaluation of performance by means of variances, whose timely reporting should maximise the opportunity for managerial action (Edwards-Nutton & Technical Information Services, 2008). In other words, variance analysis is the difference between the actual and budgeted data.